Managing Capital Outflows : Further Operational Considerations. (Policy Papers; Policy Paper ;, 2015)
The Guidance Note for the Liberalization and Management of Capital Flows (IMF 2013a) provides operational guidance to staff on the use of the Fund's institutional view on the liberalization and management of capital flows (Box 1). It discusses appropriate policies with respect to the liberalization of capital flows and the management of disruptive capital inflows and outflows. With respect to capital outflows, the institutional view considers that capital flow management measures (CFMs) may be appropriate in crisis-type circumstances or, in the context of capital flow liberalization, if countries find that they have liberalized prematurely and are unable to handle the resulting capital flows. In non-crisis-type circumstances, the guidance considers outflows as being appropriately handled by macroeconomic, financial, and structural policies. It is intended to mirror the policy advice with respect to capital inflows. The guidance is, however, relatively brief and would benefit from some elaboration to lay out the possible configurations of policies in the context of the institutional view. This note seeks to provide such an elaboration, which is particularly relevant as capital outflows are becoming a more relevant policy challenge.